Análise do aproveitamento energético do biogás do aterro sanitário metropolitano oeste em Caucaia sob a perspectiva do mecanismo de desenvolvimento limpo - Linard, André de Freitas Gomes (2010)
The great generation of Municipal Solid Waste (MSW) in Brazil has become a convergent focus of concern of Government and society by the evidence that it’s not given appropriate treatment or final disposal to the large part of this amount of garbage. Disposed in landfills, controlled and sanitary landfills, MSW, after the action of degradation mechanisms, emit polluting gases into the atmosphere, mainly methane (CH4) and carbon dioxide (CO2), which contribute to the aggravation of the phenomenon of the Greenhouse Effect. The Kyoto Protocol, a document adopted under the United Nations Framework Convention on Climate Change (UNFCCC), set up limits on emissions of Greenhouse Gases (GHG) for industrialized countries and to effectively get this purpose instituted a flexible instrument called Clean Development Mechanism (CDM). It established that the developed nations that had troubles to accomplish their quotas for reducing emissions could invest in GHG reducer or remover projects in developing nations. This research analyzed the energetic utilization of the biogas from the Caucaia West Metropolitan Sanitary Landfill (ASMOC) through the criteria of the CDM, proceeding firstly the analysis of the technical viability of the energetic utilization of Landfill Gas (LFG) as well as the CDM rules, which are: i) Baseline, definition of the whole GHG emissions in the absence of the project; ii) Additionality, verification of the project GHG reducer or remover feature, ie, reductions must be additional after the project implantation; iii) economic viability linked to the accounting of revenue from the Certified Emission Reductions (CERs), a negotiable deed in the Carbon Market that proves and registers the quantity of GHG avoided by the project; iv) verification of the project contribution to Sustainable Development. It was used for the calculation of the biogas generated in ASMOC and power available from the LFG energetic conversion the software Biogás – Geração e Uso Energético (Aterros-Versão 1.0) and to evaluate the undertaking economic viability analysis was performed based on Net Present Value (NPV) and Internal Rate of Return (IRR). The results demonstrated the technical and economic viability of the energetic utilization of ASMOC biogas, with the implementation of electricity generating plant whose output is 10MW, emissions reduction of approximately 9 million tons of carbon dioxide as well as the CDM be a powerful tool in promoting and making possible energetic landfill projects, reflecting positively in terms of environmental, economic and social (Sustainable Development triad).